Dampak Permainan Bola Keranjang & Bowling Terhadap Gerak Tubuh Anak - Ditania Nanda; Adi Wijayanto (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2022)
This research is motivated by the teacher's lack of awareness of gross motor development of the upper limbs in children, most teachers only provide stimulation to the gross motor development of children's lower limbs such as running, and jumping. Gross motoric upper limbs need to be developed because by training gross motoric upper limbs in children can train children's focus on objects, and can train children's hand-eye coordination. The aims of this study were: to determine the effect of basketball games on the gross motor development of the upper limbs in Dharma Wanita Kindergarten, to determine the influence of bowling  on the gross motor development of the upper limbs at Ichlashul Amal Kindergarten, to determine the mutual influence between the games. basket ball and bowling on gross motor development of the upper limbs in grade B children. This study used a quantitative approach with a quasi-experimental design type of research. The population in this study amounted to 30 children from 3 schools. The results of the ANOVA test obtained sig 0.000 < 0.05 which means H1 accepted andHo rejected and the post hoc obtained sig 0.558 > 0.05 which means that there is an influence from both games to develop gross motor skills of upper limbs in grade B children.